Clinical practice: intravenous thrombolysis in a patient with active cancer who experienced wake-up stroke. Issue 3 (March 2021) - Wu, Siting; Xing, Zengluan; Lin, Jiacai; Liu, Hui; Cui, Fang; Xu, Rui
After reviewing the diagnosis and treatment process of a patient with active cancer who experienced wake-up stroke, we have summarized the clinical manifestations, laboratory examination results, imaging features, pathological results, and treatment in this report. Patients with active cancer who experience wake-up stroke often have mild neurological deficits at the time of onset. For the patient in this study, laboratory test results were mainly characterized by abnormal coagulation function and elevated tumor markers. The brain magnetic resonance imaging (MRI) images were characterized by involvement of both the arterial and venous systems. Thrombolytic therapy during the window period can improve the symptoms of neurological deficits. Overall, anticoagulation therapy was safe and effective in our patient.